Bioactive Compounds and Pharmacological Potential of Hojasen (Flourensia cernua): A Mini review - Linares-Braham, Andrea; Palomo-Ligas, Lissethe; Nery-Flores, Sendar Daniel (Plant Science Today, 2024)
Flourensia cernua, commonly known as hojasen, is a shrub that is widely distributed in northern Mexico and the southern United States. The presence of this shrub indicates the characteristic flora of the Chihuahuan desert and southern Arizona, and it is an endemic plant of the Coahuila region in Mexico. The leaves and flowers of F. cernua are commercially available in Mexican markets for preparing infusions and are used as traditional medicine, mainly for gastrointestinal disorders such as indigestion, diarrhea, stomach pain, and dysentery, among others. Several studies have shown that F. cernua extracts contain bioactive compounds that can act as antioxidants in vitro by stopping free radicals from doing damage. In addition, F. cernua extracts have antifungal activity against phytopathogenic fungi. Additionally, F. cernua extracts have demonstrated antibacterial effects against Mycobacterium tuberculosis. Also, the anti-inflammatory effect of leaf extract at different doses has been studied to see how it affects the production of inflammatory cytokines and nitric oxide (NO) in macrophage cultures. Therefore, identifying its components and pharmacological properties can promote its use as an adjunct or therapeutic candidate in controlling various diseases. With its potential to alleviate gastrointestinal issues, provide antioxidant protection, and inhibit fungi and bacteria, hojasen extract may prove to be a valuable addition to the treatment of many diseases. This minireview aims to expand the existing knowledge about hojasen, a semi-desert shrub that possesses different bioactive compounds belonging to families of interest such as flavonoids, sesquiterpenoids, and coumarins, hoping to arouse the interest of other researchers to further investigate the activities, properties and uses attributed to Flourensia cernua.